P-211 "Am I the Only One?" Understanding Loneliness Among Children and Adolescents with Inflammatory Bowel Disease. (March 2016) - Lawton, Rachel; Rothbaum, Robert; LaRose-Wicks, Michelle; Weissberg-Benchell, Jill; Victorson, David; Washburn, Jason
Abstract : Background: The physical symptoms and social consequences of pediatric Inflammatory Bowel Disease can be stigmatizing and isolating. For pre-adolescent and adolescent patients for whom social acceptance and sameness with peers is a paramount concern, the emotional repercussions of these symptoms and the experience of disease itself has the potential to be a significant psychological burden. At this time, limited research has assessed loneliness amongst pediatric IBD patients. This research aims to better understand the prevalence of loneliness and the factors related to its presence among children and adolescents with IBD. Methods: Data was prospectively collected from a cohort of 36 pediatric patients previously diagnosed with IBD. Loneliness was assessed with the UCLA Loneliness scale. Additional measures assessed psychosocial function (Pediatric Symptom Checklist), social connectedness (Social Connectedness Scale), medical traumatic stress (Child Revised Impact of Events Scale), prior medical history, and current disease activity. Measures are reliable and valid and included Likert-scale responses. Results: Sixty-nine percent of participants were diagnosed with CD. The mean age at participation was 13.6 years old (SD = 1.9 years, R = 10–18 years old). IBD diagnosis did not vary by gender or age. Thirty-six percent of patients were diagnosed 5+ years prior to study participation, while an additional 39% were diagnosed within the 1 to 4 years prior. One quarter of participants were diagnosed in the past 12 months. Fifty-eight percent of participants reported one or more prior inpatient hospitalizations, while 28% endorsed prior surgical history. One third of participants reported that they "sometimes" or "always" feel alone, while 31% reported that they "rarely" or "never" feel as if they have a lot in common with the people around them. Total reported loneliness varied significantly by gender (f (34) = −4.0, P = 0.000), with female participants reporting significantly greater symptoms (M = 46.6, SD = 9.9) than their male peers (M = 33.1, SD = 10.2). Loneliness was significantly correlated with symptoms of traumatic stress related to the patient's IBD diagnosis (rs = .501, P = 0.002). Reported loneliness varied significantly by the clinical significance of the participant's psychosocial symptoms (f (34) = −4.23, P = 0.000)—those who reported clinically poor psychosocial function described significantly greater loneliness (M = 54.7, SD = 5.6) than their healthy peers (M = 35.9, SD = 10.5). Loneliness was significantly and negatively correlated with health-related quality of life (rs = −0.633, P = 0.000) and social connectedness (rs = −0.518, P = 0.001). Conclusions: Loneliness was commonly reported among participants. While normative to a degree amongst all adolescents, pediatric patients with IBD may be at elevated risk. This may be particularly true for patients who present with anxiety related to their diagnosis, additional psychosocial/emotional symptoms, poor health-related quality of life, and/or poor social relationships. Given the strong association between loneliness and significant psychosocial symptoms, care providers should be sensitive to symptoms of loneliness amongst pediatric patients and be mindful that these symptoms may indicate greater emotional and social concerns.